Bringing Maggie home : a novel - Sawyer, Kim Vogel (WaterBrook, 2017)
"Ten-year-old Hazel takes her three-year-old sister to pick berries in a blackberry thicket in 1943, and only one of them comes home again. Young Hazel's world crumbles, the weight of the guilt from that colors every relationship in her life for the next seventy years. But now Hazel's granddaughter Meghan is a cold case agent and has an opportunity to investigate this very personal family mystery. What she uncovers could provide healing for three generations of women"--